The repatriation of African heritage: shutting the door on the imperialist narrative (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2023)
This article is written in recognition of the repatriation movement, which is going through a renaissance in relation to the cultural heritage of African peoples. The collecting of African cultural heritage without free, prior and informed consent was a feature of colonialism. This article highlights the vulnerability of past and present African heritage in the light of the ‘imperialist narrative’. The imperialistic narrative accompanied the act of colonialism in Africa and enabled the taking of African heritage to public and private collections in Europe and America where many remain. Much of the heritage was displayed as an African ‘curiosity box’ which helped to support the now discredited idea of a hierarchy of peoples. This articleargues that until there is a steady stream of African heritage returning home to Africa the narrative will continue to impact in situ African heritage including natural resources. Until museums repatriate African heritage unreservedly, the ‘imperialist narrative’ will exclude the corollary narrative of African Renaissance. The article examines potential restitution/repatriation mechanisms for African peoples and states for the return of their cultural heritage, drawing on the UNESCO conventions, the African Union Charter for African Cultural Renaissance, the Sarr and Savoy Report, ‘Restitution of African Cultural Heritage. Toward a New Relational Ethics’, the Report of the Expert Mechanism on the Rights of Indigenous PeoplesRepatriation of ceremonial objects, human remains, and intangible resources under the United Nations Declaration on the Rights of Indigenous Peoples’ and the ECOWAS 2019/2023 Action Plan on the return of cultural properties to their countries of origin.